Sex differences in the risk factors of disability among community-dwelling older adults with hypertension: Longitudinal results from the Health, Aging, and Retirement in Thailand study (HART) - Wongsin, Utoomporn; Chen, Tuo-Yu (Frontiers in Public Health, 2023)
Background: Hypertension poses a serious health problem among Thai older adults which could subsequently lead to disability. However, little to no research has been conducted to understand modifiable risk factors of disability among community-dwelling older adults with hypertension in Thailand. Besides, sex is an important social determinant of health, but its role in disability among older adults with hypertension is less clear. Objectives: This study focused on community-dwelling older adults with hypertension in Thailand and investigated predictors of disability and examined sex differences in the risk factors that were associated with disability in this population. Methods: Longitudinal data were from the Health, Aging, and Retirement in Thailand (HART) survey (2015-2017; N = 916). The outcome variable was difficulty with the activity of daily living at follow-up. Potential risk factors included sociodemographic information, health behaviors/health status, and disability at baseline. Descriptive analysis and logistic regression analysis were employed to analyze the data. Results: Most of the participants were female and between aged 60 and 69 years old. Being in an older age group (OR= 1.78, 95% CI: 1.07-2.97, p<0.05), having more chronic conditions (OR=1.38, 95% CI: 1.10-1.73, p<0.01), experiencing obesity (OR= 2.02, 95% CI: 1.11-3.69, p<0.05), and having disability at baseline (OR=2.42, 95% CI: 1.09-5.37, p<0.05) significantly predicted disability at 2-year follow-up among community-dwelling Thai older adults with hypertension. The effects of these risk factors on disability at follow-up did not differ by sex. However, different risk factors of disability were observed across sexes. Conclusion: The situations of disability among older adults with hypertension in Thailand are likely to aggravate due to the rapid aging of the population. Our analysis provided useful information regarding significant predictors of disability and sex-specific risk factors of disability. Tailored promotion and prevention programs should be readily available to prevent disability among community-dwelling older adults with hypertension in Thailand.